Implications of Shift Work on Health of Women Workers in an Electronic Factory - Hashim, Zailina; Abd. Ghani, Mat Yusof (1986)
A study on the health effects of shift work among Malay workers was conducted at an electronic factory in Hulu Kelang, Selangor. The comparative study was done on shift and regular workers. A sample consisting of 100 shift workers which made up 20% of the' total shift work first, and 40 regular workers which made up about 80% of the regular workers were selected. Firstly, purposive sampling was done where all the respondents selected we.re unmarried Malay women who worked as production operators. Later, simple random sampling was carried out to select the respondents. Data was collected using questionaire based on the objectives. The respondents selected were in the age range, 1.9.- 22 years. The respondents had until secondary school level education and had been working from 1 - 5 years with a monthly income of about $350 - $400. Statistical tests revealed significant differences in health of shift and regular workers. Shift work affects their sleeping patterns and·mealtime. The disturbance has a negative impact on the physiology of the workers. Emotionally, the shift workers are not satisfied with the working conditions as well as the working system. Besides' this, shift work also affects the social activities of workers, such as recreation, relationship~ with other members of the family, relatives and friends.